Design of Two Novel Dual Band-Notched UWB Antennas - Bing Li; Jing-song Hong (International Journal of Antennas and Propagation)
Two novel dual band-notched ultra-wideband (UWB) printed monopole antennas with simple structure and small size are presented. The size of both antennas is 25×25×0.8 mm3. The bandwidth of one of the proposed antenna can be from 2.7 GHz to 36.8 GHz, except the bandwidth of 3.2–3.9 GHz for WiMAX applications and 5.14–5.94 GHz for WLAN applications. The bandwidth of the other is ranging for 2.7 to 41.1 GHz, except the bandwidth of 3.2–3.9 GHz for WiMAX applications and 4.8–5.9 GHz for WLAN applications. Bandwidths of the antennas are about 512% and 455% wider than those of conventional band-notched UWB antennas, respectively. In addition, the time-domain characteristics of the two antennas are investigated to show the difference between both antennas.